Sound source localization of filtered noises by listeners with normal hearing: A statistical analysis - Yost, William A. (Acoustical Society of America, 2013)
Several measures of sound source localization performance of 45 listeners with normal hearing were obtained when loudspeakers were in the front hemifield. Localization performance was not statistically affected by filtering the 200-ms, 2-octave or wider noise bursts (125 to 500, 1500 to 6000, and 125 to 6000 Hz wide noise bursts). This implies that sound source localization performance for noise stimuli is not differentially affected by which interaural cue (interaural time or level difference) a listener with normal hearing uses for sound source localization, at least for relatively broadband signals. This sound source localization task suggests that listeners with normal hearing perform with high reliability/repeatability, little response bias, and with performance measures that are normally distributed with a mean root-mean-square error of 6.2° and a standard deviation of 1.79°.